Increasing Students’ Speaking Skill Through Narrative Storytelling At Smp Muhammadiyah 2 Cirebon - Siti Komala (KOMVERSAL, 2023)
ABSTRACTStorytelling is a technique to increase monologue speaking skill. Some types of text can be used in storytelling such as recount, and narrative text. The writer used narrative story for this research because the students learnt the importance of how to communicate ideas and interact with the others completed by moral message on it. They developed their vocabulary and learnt how to use and express the words and sentences. The objectives of this research are to determine (1) whether the use of narrative storytelling increase the eighth grade students’ speaking skill (2) to describe how the students’ responses after they learnt storytelling. The population of this research is the eighth grade of SMP Muhammadiyah 2 Cirebon. The writer used pre-experimental research in finding her research. One group pretest-posttest design from McMillan (2001) was used in this research in order that she chose the eighth grade A for her sample in this study. A test and some question in interview were given to them. The data was analyzed by t-test formula from McMillan. The writer got t-acount (4.2987) is higher than t-table (2.0281), the distinction between t- a and t-t was about 2.2706. The data proved through testing of hypothesis was accepted that there was the increasing of students’ speaking skill after storytelling was used in teaching speaking to the eighth grade of SMP Muhammadiyah 2 Cirebon. The students’ responses after they learnt storytelling, all of them were excited in spite of lack of vocabulary, applied past tense, and how to express and intonation the certain words correctly were the problems for most of the students in storytelling. The writer gave motivation, stimulation, and media of teaching to support speaking skill study.Key words: Storytelling, Narrative, and Speaking Skill